Molecular Analysis of Xa4 and xa5 Resistance Genes Involved in the Response to Bacterial Lieaf Blight in Conventional Rice Lines in Burkina Faso - Kone, Soumana; Konate, Abdourasmane Kadougoudiou; Barro, Antoine; Wonni, Issa (Discoveries in Agriculture and Food Sciences, 2025)
Rice is a staple crop in Burkina Faso, but its production is threatened by bacterial leaf blight, which caused yield losses of up to 50% between 1998 and 2004. To address this issue, new rice varieties have been developed through crosses with IRBB lines carrying multiple resistance genes, particularly Xa genes. This study aimed to identify the presence or absence of Xa4 and xa5 resistance genes in these new varieties and their parental lines. The plant material consisted of 12 rice lines, including five new varieties and their respective parents. Molecular detection was performed using PCR-based markers ; MP1 for the Xa4 gene and RM122 for the xa5 gene. Genomic DNA was extracted using a modified Permingeat protocol, and amplification products were analyzed by electrophoresis on 3.5% agarose gel in 0.5X TAE buffer. Results showed that six lines carried the xa5 gene: the parents CT21376-F3-9-1, IRBB60, and the new varieties AR19L018-F4-27, AR19L018-F4-22, and AR19L025-F4-117. The Xa4 gene was detected in seven lines: the parents IRBB50, IRBB60, CT21376-F3-9-1, and the new varieties AR19L018-F4-22, AR19L018-F4-27, AR19L021-F4-99, and AR19L025-F4-117. Notably, three new varieties AR19L018-F4-22, AR19L018-F4-27, and AR19L025-F4-117 possess both Xa4 and xa5, suggesting a pyramiding of resistance genes that may provide durable protection against multiple Xanthomonas oryzae pv. oryzae strains. Field trials in disease-endemic areas are recommended to validate their resistance and agronomic performance.